Penanggulangan Kejahatan Perompakan Laut di Indonesia Berdasarkan Hukum Pidana Internasional - DAVID HANS KRISTIAN TAMBUNAN; Krisencia Indah Permata; Dela Ulianda Simanjuntak; Muhammad Firdaus; FRIANDOLLY JORGIT TUA MANIK (Jurnal Hukum Statuta, 2022)
In the Indonesian Dictionary (KBBI), pirates have the meaning of pirates. Pirates or in other words, ship hijacking is a form of maritime crime. It is very familiar to us to know the piracy of the high seas carried out by foreign and domestic ships. The crime of piracy is a serious threat to international security. The crime of piracy at sea is an act of violence carried out for personal gain by the crew or passengers of a ship and directed on the high seas against another ship in a place outside the jurisdiction of any country. This article aims to analyze the jurisdiction of a country to reduce the number of maritime piracy crimes in Indonesia. This research uses doctrinal research. Doctrinal legal research is research on law that is conceptualized and developed on the basis of the doctrine adopted by the drafter and/or developer. Sources of legal information use primary legal materials (relevant regulations and documents) for further qualitative analysis. The approach used is legislation, conceptual, and analysis in helping to solve the problem formulation. To try the perpetrators of the crime of piracy, international law has handed over its authority to all countries, namely the application of the principle of universal jurisdiction.